2021
DOI: 10.31729/jnma.6722
|View full text |Cite
|
Sign up to set email alerts
|

C-Shaped Canal in Second Molar of Mandible among Cases of Cone Beam Computed Tomography in Tertiary Care Centres: A Descriptive Cross-sectional Study

Abstract: Introduction: C-shaped canal configuration is mostly found in the mandibular second molar. The morphological characteristic of a C-shaped canal is the presence of a fin or web connecting the individual canal, making it difficult for cleaning, shaping, and obturation. The objective of this study was to find out the prevalence of C-shaped canal in mandibular second molar among cases of Cone Beam Computed Tomography in tertiary care hospitals. Methods: The descriptive cross-sectional study was conducted in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…[19][20][21][22] The prevalence of C-shaped canal variation varies between 4.6% and 14.32% in different populations such as Brazil, Portugal and Nepal except East Asian countries. 1,3,6,9,23,24 In the Turkish subpopulation, the prevalence of MSM teeth with C-shaped canal variation was reported as 10.7% by Sönmez Kaplan et al, 7.7% by Kaya Büyükbayram et al, 8.9% by Helvacioglu-Yigit and Sinanoglu and 4.1% by Duman et al 15,16,25,26 In our study, the prevalence of C-shaped canal configuration in MSMs was determined as 6.94%. This result is similar to the average of the prevalence values found in previous studies in Turkish society.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…[19][20][21][22] The prevalence of C-shaped canal variation varies between 4.6% and 14.32% in different populations such as Brazil, Portugal and Nepal except East Asian countries. 1,3,6,9,23,24 In the Turkish subpopulation, the prevalence of MSM teeth with C-shaped canal variation was reported as 10.7% by Sönmez Kaplan et al, 7.7% by Kaya Büyükbayram et al, 8.9% by Helvacioglu-Yigit and Sinanoglu and 4.1% by Duman et al 15,16,25,26 In our study, the prevalence of C-shaped canal configuration in MSMs was determined as 6.94%. This result is similar to the average of the prevalence values found in previous studies in Turkish society.…”
Section: Discussionsupporting
confidence: 44%
“…30 In the middle third of the root, Shemesh et al C2 and C3 configuration, Joshi et al and Nejaim et al C1 configuration, Sönmez Kaplan et al reported that the C2 configuration was the most prevalent. 1,9,16,23 We observed the most common configuration as C2 in the same region, but there was no statistically significant difference. Shemesh et al reported that the C1 configuration is common in the apical third of the root, while Joshi et al and Sönmez Kaplan et al stated that C2 and C4, C4 configurations are observed frequently, respectively.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…12 Different populations show different incidence of C-shaped canals. 13 The differences can be due to location, sample size and morphological changes in oral mucosa. 14 The current study recorded C-shape canals to be 20 % in our populations.…”
Section: Resultsmentioning
confidence: 99%
“…The most common root canal system of maxillary first molars was three roots with four canals[ 12 ]. The DB and palatal roots of maxillary first molars usually have only one root canal, while the MB root has two or more canals system[ 13 , 14 ]. MB2 canals are detected in 30%-95% individuals in different populations[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%